Electrocochleography in children with auditory synaptopathy/neuropathy: Diagnostic findings and characteristic parameters. Issue 2 (February 2015) - Stuermer, Konrad Johannes; Beutner, Dirk; Foerst, Astrid; Hahn, Moritz; Lang-Roth, Ruth; Walger, Martin
Abstract Introduction The early diagnosis of AS/AN in children remains challenging because it exclusively relies on the detection of OAE and/or CM, while ABR are pathologically changed or missing. The aim of our study was to ensure the diagnosis of AS/AN, demarcate it to an outer hair cell damage and possibly differentiate between pre- and postsynaptic pathologies. Methods We retrospectively evaluated the transtympanic ECochG results of ten children with AS/AN and compared them to a matched group with SNHL and without any signs of AS/AN. We analyzed the thresholds, latencies and – as a new parameter – the amplitude ratio between CAP and SP. Results CM and SP thresholds were significantly lower than CAP thresholds in AS/AN patients and significantly lower than SP and CM thresholds in SNHL patients with comparable CAP thresholds. The CAP/SP ratio of amplitudes in SNHL children was more than three times (significantly) higher than in AS/AN children. The cutoff value was set at 1.0 in order to differentiate between both groups with a 80–90% sensitivity and specifity. It was not possible to differentiate between a pre- and postsynaptic type of AS/AN in our collective. Summary and conclusion The ECochG can add valuable information for a precise differential diagnosis of AS/AN, especially in babyhood. We identified the CAP/SP ratio as a new parameter for differentiation between AS/AN and SNHL. When the CAP/SP ratio falls below 1.0, patients can be diagnosed AS/AN with high specificity and sensitivity. Significantly smaller SPL are needed to evoke SP and CM in the AS/AN group, thus showing the preserved hair cell function.